PENDEKATAN DESAIN PARAMETRIK DALAM SAYEMBARA KONSEP DESAIN GEDUNG ASEAN SECRETARIAT (ASEC) - Khidmat, Rendy Perdana (Jurnal Arsitektur ARCADE, 2018)
Abstract:. Recent trends and rapid developments in computing gives tremendous impact in many disciplines beside computer science. Architecture is one of disciplines that have undergone an evolution in paradigm as a result of this development. Parametric design is one of the approaches used in architectural design which lead to the advance circumtances in design process. This approach adopts some of designer-friendly programming language where architects can utilize unlimited computation abilities from computers in search of design solutions by designing their parametric definitions or rules. This article will discuss about the parametric approach to the design of multi-storey building buildings. The case study in this research is the design competition of ASEAN Secretariat building (ESAC) organized by Ikatan Arsitek Indonesia (IAI) Jakarta. The Grasshopper platform is used to explore for building form (form-finding) that maximize the view toward its site. A simple radiation analysis is also conducted in this design process using the plug-in called Ladybug + Honey bee and Multi-Objecive Optimization using Octopus plug-in, to look for minimal radiation that is affected by the location of the building form. Keywords: Parametrik desain, Grasshopper, Ladybug + Honey bee, Octopus Abstrak: Tren dan perkembangan yang pesat dalam komputasi banyak mempengaruhi disiplin lain diluar ilmu komputer. Arsitektur adalah salah satu disiplin yang banyak mengalami perubahan dalam paradigma pemikirannya akibat dari perkembangan ini. Parametrik desain merupakan salah satu pendekatan yang digunakan dalam desain arsitektur. Pendekatan ini mengadopsi bahasa pemrograman dimana arsitek dapat memanfaatkan kemampuan menghitung yang tidak terbatas dari komputer dalam mencari solusi desain dengan merancang definisi parametriknya. Artikel ini akan membahas mengenai pendekatan parametrik pada desain bangunan gedung berlantai banyak. Studi kasus pada penelitian ini adalah sayembara desain gedung sekretariat ASEAN Jakarta yang diselenggarakan Ikatan Arsitek Indonesia (IAI) Jakarta. Platform Grasshopper digunakan untuk mencari gubahan masa yang dapat memaksimalkan view dan bentuk terhadap tapaknya. Analisa radiasi sederhana juga dilakukan pada proses ini dengan menggunakan plug-in Ladybug + Honey bee dan Multi-Objecive Optimization dengan menggunakan plugin Octopus, untuk mencari radiasi minimal yang dipengaruhi oleh bentuk dan letak bangunan yang didesain. Kata Kunci: Parametrik desain, Grasshopper, Ladybug + Honey bee, Octopus